Pest Management in Indian forestry - Sen-Sarma, P. K.; Thakur, M. L. (Indian Forester, 1985)
India has been loosing nearly 1.5 millions hectares of forest cover annually, which is a warning for increased desertification in the Indian subcontinent. Therefore, while there is a need to increase the acreage under forest cover, it is also necessary to manage intensively our forest resources for increased productivity by following various management practices, including protection from various biological agencies. Among the various such agencies, insects constitute an important single factor, which limit the forest productivity. Various methods were evolved for controlling the forest pests right from the very inception of forest Entomology branch. This paper discusses in details the pest management strategies followed so far and the role played by each method in controlling the forest pests. Future line of researches have been indicated laying greater emphasis of well coordinated integrated pest management through multi-disciplinary or trans-disciplinary approaches.